Code Mixing Used by Niki Zefanya in Najwa Shihab’s Youtube Channel - Ni Komang Trisna Arisedani; I Gusti Ayu Vina Widiadnya Putri (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study explores the phenomenon of code-mixing as observed in the discourse of Niki Zefanya on Najwa Shihab's YouTube channel, utilizing the theoretical frameworks proposed by Muysken (2000) and Hoffman. The aim is to elucidate Niki Zefanya's motivations behind code-mixing in this context. Through a descriptive qualitative approach, the research delves into code-mixing practices on social media platforms, particularly YouTube, seeking to deepen our understanding of this linguistic phenomenon. Data collection involved meticulous observation and note-taking during the YouTube video